Rotavirus Infection among Diarrhoeal Children under 10 Years of Age Visiting a Children’s Hospital in Kathmandu, Nepal - Khadka, Rama; Sherchand, Jeevan Bahadur; Basnyat, Shaila; Shrestha, Ranju; Adhikari, Nabaraj (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The present study was conducted to assess the rate of rotavirus causes of diarrhoea among children under 10 years of age visiting a children’s hospital in Kathmandu, Nepal. Methods: This study was carried out from October 2010 to July 2011. During the study, a total of 1068 diarrheal stool samples were collected from inpatient and outpatient department of children less than 10 years of age attending Kanti Children’s Hospital and processed in Public Health Research Laboratory, Tribhuvan University Teaching Hospital (TUTH). About 5 ml of fresh diarrhoeal stool samples was collected and were transferred into vials which were preserved by adding buffer solution for detection of rotavirus. Samples for rotavirus antigen detection were detected by using Enzyme Immuno Assay. Data were entered into Microsoft excel and SPSS and analysis was done employing Chi-square test. Results: Among 1068 total cases, 22.0% (235/1068) children were infected with rotavirus which was found to be highest in inpatient (26.2%) with severe case (37.1%) then outpatients (12.1%). Rotavirus were found to be highest in male children (22.9%) under 2 years (23.8%) of age group. Among all season, the rotavirus infection was highest in winter seasons (29.6%) followed by spring season (26.7%) and others. According to father occupation and mother education, the prevalence of rotavirus was found to be high in children with fathers having occupation labor (27.8%) and found to be higher in children with illiterate mother (38.9%). Conclusion: The routine diagnosis of rotavirus in Nepal is not done. So it can be concluded that routine stool examination should include detection of Rotavirus antigen in diagnosis of acute pediatrics diarrhoeal illness which helps in management for diarrhoeal population.